Virtual DC machine: an inertia emulation and control technique for a bidirectional DC–DC converter in a DC microgrid. Issue 6 (11th April 2018) - Samanta, Soumya; Mishra, Jyoti Prakash; Roy, Binoy Krishna
Abstract : In a DC microgrid (DCMG), the DC bus voltage is vulnerable to the power fluctuations caused by the variations of intermittent renewable energy sources and local loads. A concept is developed to operate a bidirectional DC–DC converter as a DC machine to mimic the inertia characteristic of a DC machine and regulate the DC bus voltage fluctuations during power fluctuations of the DCMG. The concept of operating a bidirectional DC–DC converter as a DC machine can be termed as virtual DC machine (VDCM). The proposed concept of a VDCM is basically a control technique for a bidirectional DC–DC converter, which is derived from the theory of the DC machine operation and its speed control technique. The implementation, operation, controller design and dynamics of VDCM are also discussed. A VDCM can be easily operated in both generating and motoring mode also. Being free from comparatively slower mechanical devices, a VDCM can switch over from one mode to another very quickly. Hence, it provides a useful way to control the storage devices in microgrid applications.